EMPOWERING POLITENESS IN MAKING PROTEST: A CRITICAL DISCOURSE STUDY IN YOUNG MOSLEM LITERATUTE AND ITS PEDAGOGICAL VALUES - Dahlan, Dahlan (Elite : English and Literature Journal, 2025)
This study explores the concept of empowering politeness in protest discourse within young Muslim literature, employing a critical discourse analysis (CDA) framework. It examines how politeness strategies are used not to soften resistance, but to assert agency, uphold moral authority, and engage in constructive dissent. The study employs a qualitative approach, using Critical Discourse Analysis (CDA) to examine a corpus of texts written by young Muslim authors. These texts cover two novel narratives, reflecting a Moslem sociocultural context. Through close textual analysis, the results of the study showcase how the authors empower protest not as an act of aggression, but as a principled stance that aligns with religious and cultural norms. The results of the study also show how linguistic choices and strategies reflect etiquette (adab) and wisdom (Hikmah) values of respect, empathy, and ethical engagement, even within confrontational contexts. The research results further highlight the pedagogical potential of such texts in educational settings. They offer rich material for teaching critical literacy, intercultural communication, and ethical reasoning. Through the lens of empowering politeness, students can learn to articulate dissent responsibly. This study advocates for the integration of diverse voices and values in both literary appreciation and language education.